Kontestasi Ma’had Aly antara Kualitas dan Formalitas - Wafa, Ali (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Since being established as a formal institution through PMA (Minister of Religion Regulation) number 32 of 2020, Ma'had Aly has experienced a dilemma between surviving as an institution that has academic independence or following the standardization of government institutions. The regulation requires stakeholders to take policies that can determine the future of Ma'had Aly. Meanwhile, Ma'had Aly Salafiyah Syafiiyah Situbondo, Ma'had Aly Nurul Jadid Probolinggo and Ma'had Aly Nurul Qodim Probolinggo carried out different strategies in responding to the PMA. Salafiyah Syafiiyah represents an institution with a stable service system, Nurul Jadid has a dynamic character and Nurul Qodim is strategic. Ma'had Aly is an institutionalization of the intellectual tradition of pesantren-campus with a pesantren character as an answer to the fading motivation of students in mastering the turath books (salaf books). Ma'had Aly has more systematic levels, paths, and types compared to Islamic boarding schools. When compared with higher education, ma'had aly has the distinction of mastering turath books and is based on pesantren. The ma'had aly contestation has a strategic position in achieving its institutional goals. The distinction of ma'had aly lies in the standard of inputs, morality, academic, and takhassus. This study intends to unravel the response of ma'had aly as a system in maintaining its identity as a tafaqquh fi al-din institution amid formal legal demands and market penetration. The research question that will be the focus of the discussion is how ma'had aly integrates quality and formal standards.